Financial Reform and Monetary Control in Indonesia. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes the evolution and effectiveness of Indonesia's monetary control system following the financial reforms implemented since 1983. These reforms entailed the abolition of interest rate and credit ceilings, a change in the central bank's funding role, the introduction of new instruments of indirect monetary control, and measures to develop money markets. The new monetary control system was conducive to a more integrated and more competitive financial system and helped achieve the external balance objective. However, the pace of liberalization of money market rates was constrained by the choice of policy mix to deal with economic shocks.